Factors on voluntary accounting information by Greek companies - Αποστόλου Απόστολος (SPOUDAI Journal of Economics and Business, 2000)
This paper reports on voluntary accounting disclosure practices of Greek listed corporations and relates the extend and quality of disclosure to firms variables such as size, financial leverage, age, share marketability and proportion of asset in place. The extent and quality of disclosure have been measured by the average of scores given by 43 Greek Certified Public Accountants. Studying the voluntary disclosure of Greek firms, the paper provides new insights into factors behind voluntary disclosure choices. Disclosure varies widely within a sample of 36 Greek manufacturing firms listed on the Athens Stock Exchange. According to expectations, the extent and quality of disclosure is found to be significantly and positively related to the firm size, whereas the innovation of the paper rests with the found relationship between disclosure and share marketability and the non-significant association of disclosure with financial leverage, firm age and asset in place. JEL Classification: M40, G14